2014
DOI: 10.1177/0333102414550419
|View full text |Cite|
|
Sign up to set email alerts
|

Triptan use in Italy: Insights from administrative databases

Abstract: Our data indicate that approximately 10% of all triptan users in the Italian population are potentially at risk for MOH. An approach based on drug prescription databases could be useful to identify patients at risk for MOH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 20 publications
5
20
1
Order By: Relevance
“…The Dutch study revealed that 60% of the overusers were in the fifth and sixth decade of life. 32,33 Another epidemiological study described the high prevalence of ergot users and overusers in an older population, 34 but in our study we only found a low prevalence of ergot overusers (2.9%). A prospective study showed that triptan overusers outnumbered ergot overusers in the MOH population, hence triptan was the most common drug that caused MOH.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…The Dutch study revealed that 60% of the overusers were in the fifth and sixth decade of life. 32,33 Another epidemiological study described the high prevalence of ergot users and overusers in an older population, 34 but in our study we only found a low prevalence of ergot overusers (2.9%). A prospective study showed that triptan overusers outnumbered ergot overusers in the MOH population, hence triptan was the most common drug that caused MOH.…”
Section: Discussioncontrasting
confidence: 66%
“…Two other epidemiological studies also reported that triptan overusers were older than non‐overusers. The Dutch study revealed that 60% of the overusers were in the fifth and sixth decade of life …”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed that among recognized migraineurs few subjects are submitted to specific treatment [5]. In a recent investigation, only from 0.7 to 1.0 % of the analyzed population on migraine subjects used triptans [6], while in other studies the percentage varied between 3.0 and 19 % [7,8].…”
Section: Introductionmentioning
confidence: 91%
“…Furthermore, among the four provinces with a monthly quantity limit of 6 units, the prevalence of patients exceeding these limits differed considerably. In Saskatchewan, only 2.1% of patients 42 (12)(13)(14)(15)(16) 24 (12)(13)(14)(15)(16) †In accordance with institutional privacy policies, data suppressed to avoid residual disclosure of small cells. ‡P value for comparison of prevalence of triptan use between provinces <.001.…”
Section: Resultsmentioning
confidence: 99%